WX20120108, a novel IAP antagonist, induces tumor cell autophagy via activating ROS-FOXO pathway - Ding Rui; Wang Xin; Chen Wei; Li Zhi; Wei Ai-li; Wang Qing-bin; Nie Ai-hua; Wang Li-li (Acta Pharmacologica Sinica; Vol 40, No 11 (November 2019): Acta Pharmacologica Sinica, 2019)
Recently, inhibitor of apoptosis proteins (IAPs) and some IAP antagonists were found to regulate autophagy, but the underlying mechanisms remain unclear. WX20120108 is an analogue of GDC-0152 (a known IAP antagonist) and displays more potent anti-tumor and autophagy-regulating activity in tumor cells, we investigated the regulatory mechanisms underlying WX20120108-induced autophagy. Using molecular docking and fluorescence polarization anisotropy (FPA) competitive assay, we first demonstrated that WX20120108, acting as an IAP antagonist, bound to the XIAP-BIR3, XIAP BIR2-BIR3, cIAP1 BIR3, and cIAP2 BIR3 domains with high affinities. In six cancer cell lines, WX20120108 inhibited the cell proliferation with potencies two to ten-fold higher than that of GDC-0152. In HeLa and MDA-MB-231 cells, WX20120108 induced caspase-dependent apoptosis and activated TNFα-dependent extrinsic apoptosis. On the other hand, WX20120108 induced autophagy in HeLa and MDA-MB-231 cells in dose- and time-dependent manners. We revealed that WX20120108 selectively activated Foxo3, evidenced by Foxo3 nuclear translocation in both gene modified cell line and HeLa cells, as well as the upregulated expression of Foxo3-targeted genes (Bnip3, Pik3c3, Atg5, and Atg4b), which played a key role in autophagy initiation. WX20120108-induced autophagy was significantly suppressed when Foxo3 gene was silenced. WX20120108 dose-dependently increased the generation of reactive oxygen species (ROS) in HeLa cells, and WX20120108-induced Foxo3 activation was completely blocked in the presence of catalase, a known ROS scavenger. However, WX20120108-induced ROS generation was not affected by cIAP1/2 or XIAP gene silencing. In conclusion, WX20120108-induced autophagy relies on activating ROS-Foxo3 pathway, which is independent of IAPs. This finding provides a new insight into the mechanism of IAP antagonist-mediated regulation of autophagy.